Microvesicle-mediated release of soluble LH/hCG receptor (LHCGR) from transfected cells and placenta explants - Randeva Harpal; Stanley Paul F; Chambers Anne E; Banerjee Subhasis (BMC, 2011)
Abstract Placental hCG and pitutary LH transduce signals in target tissues through a common receptor (LHCGR). We demonstrate that recombinant LHCGR proteins which include the hormone-binding domain are secreted from transfected cells and that natural LHCGR is also secreted from human placental explants. LHCGR recombinant proteins representing varying lengths of the N-terminal extracellular domain were expressed in Chinese Hamster Ovary cells in suspension culture. Secretion was minimal up to 72h but by 96h 24-37% of the LHCGR had been released into the culture medium. The secreted proteins were folded and sensitive to glycosidases suggesting N-linked glycosylation. Secretion was independent of recombinant size and was mediated via structurally defined membrane vesicles (50-150nm). Similarly cultured human early pregnancy placental explants also released LHCGR via microvesicles. These studies provide the first experimental evidence of the possible mechanistic basis of the secretion of LHCGR.